Game activity and physiological responses of young tennis players in a competition with 2 consecutive matches in a day - Gallo-Salazar, C.; Del Coso, J.; Sanz-Rivas, D.; Fernandez-Fernandez, J. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To determine whether the game activity and physiological responses of young tennis players differed depending on the session of play (eg, morning [MOR] vs afternoon [AFT]) and the final match outcome (eg, winners vs losers) during a simulated competition with 2 matches on the same day. Methods: A total of 12 well-trained male tennis players (age 14.5 [0.8] y) took part in a simulated competition of two 3-set matches separated by 3 h. All the matches were video recorded, and the participants were monitored using 10-Hz global positioning system units including a heart-rate monitor. Effect-size (ES) statistics were used to investigate the magnitudes of the differences. Results: During the AFT matches, in absolute terms, players covered longer total distance (ES=moderate) and ran more distance between 0 and =4 m/s (ES=small to large) than in MOR matches. Total duration was also longer (ES=large) in the AFT, where the rest time between rallies was also longer (ES=very large). Heart rate was similar during AFT and MOR matches, but higher rates of perceived exertion (ES=moderate) were reported in the AFT. Only peak running velocity was observed to be likely higher for losers than for winners (ES=small). Conclusions: Game activity and physiological responses of young tennis players differ when 2 consecutive matches are played on the same day. These data might help elucidate the need for specific precompetition training loads and/or between-matches/sessions recovery strategies when facing overloaded competitions.